Conditions for successful implementation and transferability of good practice policies and multi-component interventions for dietary, physical activity and sedentary behaviours across Europe - Hayes, Catherine (My University, 2016)
To gain a better insight into the facilitators and barriers to successful implementation and transfer of multi-component interventions and policies addressing diet, physical activity (PA) and/or sedentary behaviours (SB) across Europe
DEDIPAC (Determinants of Diet and Physical Activity) Ireland. One day National Symposium
Keywords: International Development; Making Ireland; Health